Non-Linear Effects of Intellectual Property Rights on Technological Innovation: Evidence from Emerging and Developing Countries - Loukil, Kamilia (The Economics and Finance Letters, 2020)
The protection of Intellectual Property Rights (IPR) is a key determinant of innovation. Following the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), all member states of the World Trade Organization are called upon to introduce high intellectual property rights standards. Hence the importance of the issue relative to IPR. Recent studies suggest that IPR protection stimulates innovation only under certain conditions. In this study, we suppose that IPR have a positive impact on technological innovation only in countries with high levels of economic development. The objective of this study is to examine the relationship between intellectual property rights, economic development and technological innovation in the context of emerging and developing countries. To measure innovation, we use patent applications filed by residents of a given country with the United States Patent and Trademark Office. IPR is measured by the Ginarte and Park index. Panel Threshold Regression is applied to data of 55 emerging and developing countries for the period 1980-2009. The estimation results provide evidence for the existence of nonlinear relationship depending on economic development level. We conclude that « one size does not fit all ».